Socioeconomic Dynamics of Migrant Remittances and Nutritional Well-Being among Rural Esan Households in Southern Nigeria - Alenkhe, Augustine Odianonsen (NIU Journal of Humanities; Vol 11 No 1 (2026): NIU Journal of Humanities, Vol. 11 No. 1, March 2026, 2026)
The relationship between migrant remittances and household nutritional well-being has become an important lens for understanding livelihood transformation in developing societies. Among the Esan of southern Nigeria, this nexus remains underexplored despite growing migration and dependence on external income. Existing studies often emphasize economic outcomes, neglecting how remittances reshape everyday feeding behaviour and nutrition. Despite the improvement in current research there is paucity on current study this seeks to interrogates how remittance flows influence dietary practices and nutritional security among Esan households in Edo State. Adopting a cross-sectional and an expository research design, the study employed a Triangulation of both Quantitative and qualitative approach to generate the required information through the use of questionnaire and an in-depth interview guild was complementarily utilized on 726 respondents who were systematically selected through a multi-stage sampling procedure across two clusters in Esanland. The data collected were analyzed using descriptive statistics and content analysis. Findings reveals that migrant remittances exert a substantial but differentiated influence on household nutritional status as well as wellbeing among Esan communities. Secondly, socio-demographic factors such as age, occupation, and social status influences household perceived utilization of remittances in enhancing dietary diversity, food quality, and affordability, based on the above, conclusion and advocacy was deduced Keywords: Nutrition, Wellbeing, Remittances, Food security.